Analisis Kecemasan Siswa pada Pembelajaran Matematika Berbasis Problem Based Learning di SMP Negeri 3 Kota Jambi - Dewi, Sri; Simamora, Risma (Universitas Batanghari Jambi, 2022)
Mathematics anxiety is a feeling of pressure and nervousness that interferes with manipulating numbers and solving mathematical problems, both in everyday life and in the learning process. This study aims to describe the level of student anxiety in learning mathematics based on problem based learning at SMP Negeri 3 Jambi City. The subjects of this study were students of class VIII SMP Negeri 3 Jambi City, consisting of 4 classes. Each class is taken by 10 student representatives based on the 5 highest knowledge and 5 lowest knowledge. The data collection technique is by distributing questionnaires to all students who have been selected as many as 40 students. Researchers distributed questionnaires to get results/data on anxiety levels of SMP Negeri 3 Jambi City students. The researcher also conducted interviews with 8 student representatives to strengthen the research data. The results of this study indicate that the highest aspect of the student anxiety variable is the